Archimedes navigation system-guided bronchoscopic trans-parenchymal nodule access for peripheral lung nodules: a single-center experience - Yu, Ping-Tsung; Yang, Sheng Hsiung; Shih, Hui-Hsuan; Huang, Wei Ming; Jhuang, Jie-Yang; Chan, Mei-Lin; Huang, Wen-Chien (Frontiers in Oncology, 2025)
BackgroundPeripheral pulmonary lesions (PPLs) present diagnostic challenges because of their small size and distal airway location, often requiring invasive surgical biopsies. The Archimedes™ navigation system assists the bronchoscopic trans-parenchymal nodule access (BTPNA) procedure, offering a minimally invasive alternative for diagnosing PPLs.MethodsThis retrospective study evaluated the safety and efficacy of BTPNA guided by the Archimedes™ navigation system in 10 patients with single PPLs (<20 mm) and no bronchus signs. Preoperative CT scans were used to create a 3D virtual airway model, identify an optimal point of entry (POE), and plan an avascular pathway to the nodule. The procedure combined virtual bronchoscopy, real-time fluoroscopy, and radial endobronchial ultrasound (R-EBUS). Tissue samples were collected for histopathological analysis, and complications were monitored post-procedure.ResultsA total of 10 patients (median age: 54.5 years) were included, with a diagnostic yield of 70.0%. Successful diagnoses included adenocarcinoma in situ, granulomatous inflammation, and invasive adenocarcinoma. No complications were observed. The mean size of the nodular lesions in the 10 cases was 13.9 mm. Median distances were 12.9 mm from pleura to target lesion, and median tunnel length was 57.8 mm.ConclusionsThe Archimedes™ system-guided BTPNA is safe and effective for diagnosing small PPLs without bronchus signs, demonstrating precise localization and tissue sampling while minimizing invasiveness. No complications were observed, highlighting the procedure’s safety. Larger prospective studies are warranted to validate these findings and refine patient selection and procedural techniques to optimize outcomes.